A conductive carbon interlayer modified by magnetron sputtering for improved-performance lithium–sulfur batteries. Issue 62 (15th August 2017) - Zhang, Jing; Li, Heqin; Lin, Zhiwei; Tang, Qiong; Qi, Weiyu; Wang, Lulu; Zheng, Hao; Zhou, Kuan
Abstract : A carbon film was prepared by filter paper and modified by radio-frequency magnetron sputtering as a conductive interlayer for lithium–sulfur batteries. Abstract : Cathode materials (S–AC) for lithium–sulfur (Li–S) batteries were synthesised with elemental sulfur (S) and activated carbon (AC). Conductive carbon films (CF1) were prepared with filter paper and aluminum (Al) thin films were plated onto the surface of the filter paper by the method of magnetron sputtering to fabricate modified carbon films (CF2). The as-prepared carbon films were applied as conductive interlayers inserted between the cathode and the separator for Li–S batteries S/AC/CF1 and S/AC/CF2. The properties of the cathode materials and the carbon interlayers were characterized by XRD and FESEM. Electrochemical performances of three Li–S batteries with and without interlayers (S/AC/CF1, S/AC/CF2 and S/AC) were determined by alternating-current impedance, cyclic voltammetry and constant-current charge and discharge. The assessment results show that S/AC/CF2 is superior to the others with an initial discharge specific capacity of 1273 mA h g −1 at a current rate of 1C. It delivered a reversible capacity of 924 mA h g −1 after 100 cycles and the coulombic efficiency after 200 cycles is still over 95%.